Explaining the liking for drinking yoghurt: The role of sensory quality, food choice motives, health concern and product information - Pohjanheimo, Terhi; Sandell, Mari (International dairy journal, 2009)
The influence of sensory and non-sensory product characteristics and consumer-related factors, such as demographics, food choice motives, and health concern, on liking for four drinking yoghurt flavours was studied using a three-block L-partial least squares regression method. Degrees of liking for yoghurt flavours were evaluated in a consumer test ( n = 162) under two conditions: blind and with full product information available. The food choice motives of the members of the consumer panel and data on their concern for food and health were collected using validated questionnaires. Food choice motives were connected to the liking. Subjects who considered natural content, ethical concern, and health as important food choice motives perceived sourer, thicker, and more genuine yoghurt flavour as more pleasant, compared to subjects who considered convenience, price, mood, and familiarity more important, evaluated sweeter and smoother yoghurt as more pleasant.